When the Dark Lingers : The Role of Dark Triad Personality on Burnout Among Lecturers - Pramesty, Dewi Indah; Nuzulia, Siti (Journal of Educational, Health and Community Psychology, 2024)
Burnout is commonly experienced by professionals in the "helping relationship" sector, including lecturers. One of the factors contributing to burnout is an individual's personality. This study aims to investigate how Dark Triad Personality traits (narcissism, Machiavellianism, and psychopathy) influence burnout among Indonesian lecturers. The methodology of this study was cross sectional. Dark triad personality was measured using 5 scales: NPI, CNI, LPSP-I, LPSP-II, and Mach-IV. The total number of participants in this study was 260 (Male=141, female=119). They were all lecturers in Indonesia with at least two years of work experience. This study shows that Machiavellianism is the most significant predictor of negative burnout. Narcissism, both agentic narcissism and communal narcissism, significantly predicted burnout negatively. Secondary psychopathy significantly predicts burnout negatively, whereas primary psychopathy does not predict burnout. Furthermore, demographic factors such as gender, age, length of service, and job position do not predict burnout among lecturers.